2023
DOI: 10.3390/medicina59020377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enamel Matrix Derivative on Cell Spheroids Made of Stem Cells Obtained from the Gingiva on Osteogenic Differentiation

Abstract: Background and Objectives: A derivative of the enamel matrix was used to speed up periodontal regeneration, including the formation of new cementum, alveolar bone, and periodontal ligament. In this study, human gingiva-derived stem cell–derived cell spheroids were used to assess the effects of an enamel matrix derivative on cell viability, osteogenic differentiation, and mineralization. Materials and Methods: Human gingiva-derived stem cells were used to create spheroids, which were then coupled with unloaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…EMD has been recognized as a bone graft substitute and has demonstrated efficacy in promoting regeneration in intrabony and Class II mandibular furcation periodontal defects [ 23 ]. Further, it has been reported that the integration of EMD into 3D cultures enhances osteogenic differentiation in MSC spheroids, evidenced by significant increases in Alizarin Red S staining intensity and RUNX2 mRNA expression levels, suggesting a potential role in bone tissue engineering applications [ 13 ]. Nonetheless, earlier research has indicated that the outcomes of combining guided tissue regeneration techniques with EMD could exhibit considerable variability, leading to unpredictable regenerative results [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMD has been recognized as a bone graft substitute and has demonstrated efficacy in promoting regeneration in intrabony and Class II mandibular furcation periodontal defects [ 23 ]. Further, it has been reported that the integration of EMD into 3D cultures enhances osteogenic differentiation in MSC spheroids, evidenced by significant increases in Alizarin Red S staining intensity and RUNX2 mRNA expression levels, suggesting a potential role in bone tissue engineering applications [ 13 ]. Nonetheless, earlier research has indicated that the outcomes of combining guided tissue regeneration techniques with EMD could exhibit considerable variability, leading to unpredictable regenerative results [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It contains amelogenin, which stimulates osteoblast activity and promotes bone formation [ 12 ]. Combining MSCs and EMDs in a tissue engineering approach may have the potential to improve bone regeneration outcomes [ 13 ]. While traditional two-dimensional cell cultures have been widely used in research, recent advances in tissue engineering have highlighted the advantages of three-dimensional cell structures [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This emphasizes the potential advantages of exposure duration to specific chemical agents in facilitating fibroblast adhesion. EMD are derived from the porcine enamel matrix and promote new bone [ 22 ] and cementum [ 23 ] formation, making them a valuable component in periodontal regeneration.…”
Section: Discussionmentioning
confidence: 99%